Drivers of change in peak-season surface ozone concentrations and impacts on human health over the historical period (1850–2014) - S. T. Turnock; S. T. Turnock; D. Akritidis; D. Akritidis; L. Horowitz; M. Mertens; A. Pozzer; A. Pozzer; C. L. Reddington; H. Wang; P. Zhou; F. O'Connor; et al. (Atmospheric Chemistry and Physics, 2025)
Elevated concentrations of ozone at the surface can lead to poor air quality and increased risks to human health. There have been large increases in surface ozone over the historical period associated with socio-economic development. Here, the change in peak-season ozone (OSDMA8) is estimated for the first time using hourly surface ozone output from three CMIP6 models over the 1850 to 2014 period. Additional results are obtained from one model to quantify the impact from different drivers of ozone formation, including anthropogenic emissions of ozone and aerosol precursors, stratospheric ozone, and climate change. The peak-season ozone concentrations are used to calculate the risk to human health, in terms of the attributable fraction metric (the percentage of deaths from COPD – chronic obstructive pulmonary disease – associated with long-term exposure to elevated ozone concentrations). OSDMA8 concentrations are simulated to increase by more than 50 % across northern mid-latitude regions over the historical period, mainly driven by increases in anthropogenic emissions of NOx and global CH4 concentrations. Small contributions are made from changes in other anthropogenic precursor emissions (CO and non-CH4 volatile organic compounds; VOCs), aerosols, stratospheric ozone and climate change. The proportion of the global population exposed to OSDMA8 concentrations above the theoretical minimum risk exposure level (32.4 ppb) increased from <20 % in 1855 to >90 % in 2010. This has also increased the risk to human health mortality due to COPD from long-term ozone exposure by up to 20 % across Northern Hemisphere regions in the present day. Like for OSDMA8 concentrations, the drivers of the increase in the ozone health risks are attributed mainly to changes in NOx and global CH4. Fixing anthropogenic NOx emissions at 1850 values can eliminate the risk to human health from long-term ozone exposure in the near-present-day period. Understanding the historical drivers of ozone concentrations and their risk to human health can help to inform the development of future pathways that reduce this risk.